Get Connected: A Scoping Review of Advising Online Graduate Students - Meyer, Holly S; Preisman, Kristi A; Samuel, Anita (Online Learning, 2022)
The rate of online graduate education programs grows annually. Yet, dropout rates and student satisfaction rates continue to lag behind in-person programs. Advising practices may offer unique opportunities to reverse or alter these challenges. While the body of literature about undergraduate advising and online advising is robust, literature on current online graduate-level advising is sparse. Therefore, a scoping review of the literature was undertaken to answer the research question: What does the literature tell us about advising in online graduate programs? The search revealed ten relevant studies, and after conducting a thematic network analysis, two global themes and five organizing themes were presented. There are two global themes, “Create Connections” and “Know Your Program.” The “Create Connections” global theme is supported by three organizing themes: (a) Communication and Feedback, (b) Building Relationships and Community, and (c) Investment in student’s personal and academic growth. The “Know Your Program” global theme is supported by organizing themes (d) Program Requirements and Policies and (e) Technical skills. Based on the data, three recommendations are presented to aid online graduate advisors, including building trusting relationships with advisees, building a community of students, and knowing program policies, requirements, and technology platforms.